High PD-L1 expression correlates with primary resistance to EGFR-TKIs in treatment naïve advanced EGFR-mutant lung adenocarcinoma patients. (January 2019) - Hsu, Kuo-Hsuan; Huang, Yen-Hsiang; Tseng, Jeng-Sen; Chen, Kun-Chieh; Ku, Wen-Hui; Su, Kang-Yi; Chen, Jeremy J.W.; Chen, Huei-Wen; Yu, Sung-Liang; Yang, Tsung-Ying; Chang, Gee-Chen
Highlights: The level of PD-L1 expression can predict efficacy of EGFR-TKI. Higher PD-L1 expression had high incidence of primary resistance to EGFR TKI. Higher PD-L1 expression had shorter progression-free survival. Abstract: Objectives: The main objective was to investigate the relationship between Programmed cell Death-ligand 1 (PD-L1) expression levels and the frequency of primary resistance to Epidermal Growth Factor Receptor (EGFR)-Tyrosine Kinase Inhibitor (TKI) in treatment naïve advanced EGFR -mutant lung adenocarcinoma patients. Materials and methods: From 2012–2017, we enrolled advanced EGFR -mutant lung adenocarcinoma patients who displayed primary resistance to EGFR-TKI therapy, along with patients with disease control, and patients experiencing either stable disease or partial response to EGFR-TKI treatment. Results: Sixty-six patients were enrolled as the primary resistance group, while 57 patients were included as the disease control group. Fifteen-five (22.7%) patients had a PD-L1 Tumor Proportion Score (TPS) ≧50% in the primary resistance group, with only one patient (1.8%) having that score in the disease control group (P＜0.001). Twenty (30.3%) patients had a PD-L1 ≧25% in the primary resistance group, with 2 (3.5%) patients having that level in the disease control group (P＜0.001). Thirty (45.5%) patients had a PD-L1 ≧1% in the primary resistance group, with 7 (12.3%) patients at that level in the disease control group (P = 0.001). Patients with a PD-L1≧1% displayed a higher incidence of primary resistance to EGFR-TKIs than those with a PD-L1＜1% (Odds Ratio (OR), 5.95; 95% Confidence Interval (CI), 2.35–15.05; P＜0.001). The phenomenon existed still when the cutoff value was changed to both 25% (OR, 11.96; 95% CI, 2.65–53.87; P = 0.001) and 50% (OR, 16.47; 95% CI, 2.10–129.16; P = 0.008). The estimated median Progression-free Survival (PFS) rate was 7.3 months in patients with a PD-L1＜1%, 2.1 months in patients with a PD-L1≧1%, 1.8 months in patients with a PD-L1≧25%, and 1.6 months in patients with a PD-L1≧50%. Conclusions: Treatment for advanced EGFR -mutant lung adenocarcinoma patients displaying a higher PD-L1 expression level experienced a higher frequency of primary resistance to EGFR-TKIs.